The Battle For Open How openness won and why it doesn't feel like victory - Weller, Martin (Ubiquity Press, 2014)
With the success of open access publishing, Massive open online courses (MOOCs) and open education practices, the open approach to education has moved from the periphery to the mainstream. This marks a moment of victory for the open education movement, but at the same time the real battle for the direction of openness begins. As with the green movement, openness now has a market value and is subject to new tensions, such as venture capitalists funding MOOC companies. This is a crucial time for determining the future direction of open education. In this volume, Martin Weller examines four key areas that have been central to the developments within open education: open access, MOOCs, open education resources and open scholarship. Exploring the tensions within these key arenas, he argues that ownership over the future direction of openness is significant to all of those with an interest in education.